Estudio de Endomarketing para determinar la satisfacción del cliente interno en la IPS Ensalud Colombia S.A.S (2018)
The purpose of the development of this research is to measure the level of satisfaction of the internal clients of the IPS Ensalud Colombia SAS located in the city of Santiago de Cali. To achieve the achievement of this objective, the structuring of a research with an exploratory and descriptive approach was proposed. The fieldwork was done based on the survey with closed questions and a questionnaire with open questions in order to perform a Verbatim. It was carried out to all the personnel of the headquarters of Cali; the sample was of 30 internal clients and 7 clients respectively. In-depth interviews were also conducted with the manager, three bosses and three subordinates. The results show that for the internal clients surveyed the job satisfaction they have regarding the company is positive. Some variables such as communication, work environment and teamwork are variable with not so positive results, which must be prioritized in order to take improvement measures. This may mean that the company, although taking into account the needs of the staff, it is necessary to emphasize the variables such as internal communication, work climate and work in the team where they make the improvement proposals to increase the job satisfaction of employees in these variables. Finally, it is recommended to prioritize the variables that are presenting failures within the company where it contemplates: a proposal for internal communication, a proposal to improve the work climate and encourage teamwork